(untitled) (Encuentros, 2020)
Machiavelli’s narrative as one of the modern thinkers who have shaped modern political thought in the area of social sciences and politics, implies an epistemic field of great relevance that bets on the complexity of the processes/dynamics that constitute the political powers in contemporary democracies. Keywords: Machiavelli, Political Science, Democracy, Political Studies, Modernity.